Dear Punchy: Representing and Feeling Writing in Animal Crossing - Bohunicky, Kyle Matthew (Loading)

(untitled) (Canadian Game Studies Association, 2020)
This article explores how the Animal Crossing series represents and invites players to practice writing. Adopting several frameworks including media speleology, affect theory, and writing studies, this article argues that the representation of writing in the first game in the Animal Crossing series, Animal Forest, resists both the technological and gendered histories typically ascribed to writing and video games. Turning to the ways that players actually practice writing, this article suggests that affect plays a key role in the deep connections that players develop with fellow villagers through the act of letter writing. Ultimately, this article calls for further examination of writing’s role in the cultural significance of Animal Crossing and careful study of its representations in other video games.